Genetic structure in cultivated quinoa (Chenopodium quinoa Willd.), a reflection of landscape structure in Northwest Argentina - Costa Tártara, Sabrina María; Manifesto, Maria Marcela; Bertero, Héctor Daniel; Bramardi, Sergio Jorge (Springer, 2019)
Quinoa (Chenopodium quinoa Willd.), one of the main crops domesticated in the Andean highlands 1,000 of years ago, played an important role as a protein source. 35 germplasm accessions collected along the Northwest Argentina (NWA) region were studied using 22 microsatellite (SSR) markers. Results showed a great level of genetic diversity, differing from previous reports about the geographical distribution of quinoa variability. All SSR loci analysed were highly polymorphic detecting a total of 354 alleles among all populations, with an average of 16 alleles per locus. Cluster analyses grouped the accessions into four main clusters at the average genetic distance level (0.80), each of which represented a different environment of the NWA region: Puna (UHe = 0.42, ±0.07 SE), Dry Valleys (UHe = 0.27, ±0.05 SE), Eastern Humid Valleys (UHe = 0.16, ±0.04 SE) and a transition area with high altitudes between the last two environments (UHe = 0.25, ±0.03 SE). An eastward decreasing genetic diversity gradient was found. AMOVA analyses showed a strong genetic structure: a high population subdivision relative to the grouping by region (Fsr = 0.47) together with a high genetic differentiation among populations (Fst = 0.58) and a heterozygous defect (Fis = 0.63) in each of them. The variability structure, a reflection of the structure of the NWA landscapes, is discussed in connection with environmental variables.